2005
DOI: 10.2174/1568016054368214
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacologic Approach to the Prevention of Preeclampsia: From Antiplatelet, Antithrombosis and Antioxidant Therapy to Anticonvulsants

Abstract: Preeclampsia has been suggested to be a two-stage disorder of an alteration in placental perfusion (stage 1) leading to generalized vascular endothelial damage (stage 2). Because the mechanism linking the two stages remains unclear, effective primary prevention is still impossible. However, advances made in our understanding of the pathophysiology of preeclampsia have paved the way for secondary and tertiary prevention approaches.Platelets are known to be activated in early pregnancy. They also play a pivotal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Magnesium sulfate (MgSO 4 ) is used clinically for the treatment of severe pre-eclampsia and eclampsia [5]. In addition, cellular data from our group [6] and those from the other group [7] revealed that MgSO 4 possesses potent anti-inflammation capacity, as endotoxin-induced upregulation of inflammatory molecules could be inhibited by MgSO 4 .…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Magnesium sulfate (MgSO 4 ) is used clinically for the treatment of severe pre-eclampsia and eclampsia [5]. In addition, cellular data from our group [6] and those from the other group [7] revealed that MgSO 4 possesses potent anti-inflammation capacity, as endotoxin-induced upregulation of inflammatory molecules could be inhibited by MgSO 4 .…”
Section: Introductionmentioning
confidence: 72%
“…MgSO 4 is a potent vasodilator [5]. One would expect that MgSO 4 administration might cause significant decreases in blood pressure.…”
Section: Lung No and Mdamentioning
confidence: 99%
“…Resultant hypoperfusion causes release of angiogenic factors, altering maternal endothelial function and precipitating pre-eclampsia [45,46]. Other contributory factors implicated in the development of pre-eclampsia include RAAS involvement (detailed below), immune mechanisms [47,48] and release of oxidative stress products in the placenta [4951]. …”
Section: The Pre-eclampsia Spectrummentioning
confidence: 99%
“…22 Because PE and eclampsia are often associated with abnormal maternal inflammation, parenteral MgSO 4 has been an important drug for treating severe PE. 23 In the present study, to investigate whether systemic inflammation correlates with seizure activity, we established a new eclampsia-like model using electrical stimulation. We measured systolic blood pressure (SBP), proteinuria, creatinine (Cr), blood urea nitrogen (BUN), alanine transaminase (ALT) and aspartate transaminase (AST) to determine whether the model was successful.…”
mentioning
confidence: 99%